Study of the Tissue Distribution of TLQP-21 in Mice Using [18F]JMV5763, a Radiolabeled Analog Prepared via [18F]Aluminum Fluoride Chelation Chemistry - Elia A. Turolla; Elia A. Turolla; Silvia Valtorta; Silvia Valtorta; Elena Bresciani; Jean-Alain Fehrentz; Liliana Giuliano; Liliana Giuliano; Stefano Stucchi; Stefano Stucchi; Sara Belloli; Sara Belloli; et al. (Frontiers in Pharmacology, 2018)
TLQP-21 is a neuropeptide that is involved in the control of several physiological functions, including energy homeostasis. Since TLQP-21 could oppose the early phase of diet-induced obesity, it has raised a huge interest, but very little is known about its mechanisms of action on peripheral tissues. Our aim was to investigate TLQP-21 distribution in brain and peripheral tissues after systemic administration using positron emission tomography. We report here the radiolabeling of NODA-methyl phenylacetic acid (MPAA) functionalized JMV5763, a short analog of TLQP-21, with [18F]aluminum fluoride. Labeling of JMV5763 was initially performed manually, on a small scale, and then optimized and implemented on a fully automated radiosynthesis system. In the first experiment, mice were injected in the tail vein with [18F]JMV5763, and central and peripheral tissues were collected 13, 30, and 60 min after injection. Significant uptake of [18F]JMV5763 was found in stomach, intestine, kidney, liver, and adrenal gland. In the CNS, very low uptake values were measured in all tested areas, suggesting that the tracer does not efficiently cross the blood–brain barrier. Pretreatment with non-radioactive JMV5763 caused a significant reduction of tracer uptake only in stomach and intestine. In the second experiment, PET analysis was performed in vivo 10–120 min after i.v. [18F]JMV5763 administration. Results were consistent with those of the ex vivo determinations. PET images showed a progressive increase of [18F]JMV5763 uptake in intestine and stomach reaching a peak at 30 min, and decreasing at 120 min. Our results demonstrate that 18F-labeling of TLQP-21 analogs is a suitable method to study its distribution in the body.